The relation between adverse childhood experiences and later mental health among deaf adults - Marit H. Kvam; Mitchell Loeb (Scandinavian Journal of Disability Research, 2010)
The aim of this article is to describe some self-reported adverse childhood experiences and the current self-reported mental health situation among 376 adults who lost their hearing before nine years of age, and to analyse the possible link between the adverse childhood experiences and adult mental health problems. Adult members of the Norwegian Deaf Register were asked to complete a self-administered questionnaire. The analysis are focused on three aspects of negative childhood experiences: corporal punishment by at least one of the parents (reported by 36%), being frequently bullied by peers (reported by 23%) and being seriously sexually abused by known or unknown people (reported by 30%). Thirty-five percent of the respondents reported a mental health problem. Results indicated an association between the reported three negative childhood experiences and later mental health problems. Further analysis showed that having experienced two or three of the mentioned negative experiences in combination increased the probability of reporting mental health problems significantly.